Posted by **carol** on Wednesday, May 4, 2011 at 12:31pm.

(4a^3 - 7a^2) - (8a^3 + 1a^2) Subtract

= 4a^3 - 7a^2-8a^3 - 1a^3

= 4a^3 - 8a^3 - 7a^2 - 1a^2

= (4-8)a^3 - (-7 - 1)a^2

= -4a^3 - 8a^2

Is this correct?

## Answer This Question

## Related Questions

- Math, Please Help! - Ned divided a given number by 3 and then added 2. If he ...
- math - Can someone check and tell me if these are correct or not. subtract -88-...
- Math 8R - Help!!!!!!!!!!!!!!!!!!! - 14. Subtract -5 from -14 -14 - (-5) 16. ...
- math - Match the equation with the step needed to solve it. 1. 2m - 1 = 3m ...
- math - Match the equation with the step needed to solve it. 1. 2m - 1 = 3m ...
- Mathematicz (The Correct Question) - A pipe has an outer radius of 4 1/2 cm. If ...
- 3rd math - The commutative, or order, property applies to which operations? A. ...
- Algebra - How can I transform the equation 4=x-y into one that begins with "y...
- Algebra Repost - How can I transform the equation 4=x-y into one that begins ...
- Math - Can you check these questions for me? 1. Add: (3x^4-x+2)+(9x^5-x^2+x) 9x^...

More Related Questions